2012
DOI: 10.1108/17439131211238888
|View full text |Cite
|
Sign up to set email alerts
|

A cloudy day in the market: short selling behavioural bias or trading strategy

Abstract: PurposeResearch draws the distinction between noise traders and informed traders. Research also documents market biases in equity returns due to cloud cover, a non‐informational (noise) event, showing that returns decrease on cloudy days. The purpose of this paper is to investigate the trading behaviour of short‐sellers, who are considered informed traders, conditioning on the level of cloudiness, and find an increase in short selling with the level of cloudiness. Additionally, the paper finds decreases in sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The most common explanation for these phenomena is that investors' moods could be influenced by these exogenous events (e.g., due to seasonal affective disorder), which may influence their risk preferences and in turn influence investment decisions and market outcomes. Yet, Watson and Funck (2012) showed that short selling (a risky investment strategy) by professional traders actually increases on cloudy days, but not on the three prior days before the cloudy event. This suggests that professional traders do not correctly anticipate downward market movements based on weather forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…The most common explanation for these phenomena is that investors' moods could be influenced by these exogenous events (e.g., due to seasonal affective disorder), which may influence their risk preferences and in turn influence investment decisions and market outcomes. Yet, Watson and Funck (2012) showed that short selling (a risky investment strategy) by professional traders actually increases on cloudy days, but not on the three prior days before the cloudy event. This suggests that professional traders do not correctly anticipate downward market movements based on weather forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether this is because it affects traders' perceived likelihood of future events or because it affects their intrinsic willingness to bear uncertainty. Watson and Funck (2012) showed that short selling by (professional) traders increases on cloudy days, suggesting that they are more willing to bet against stocks going up. In the light of our definition, this suggests that the impact of cloudiness on stock returns is caused by a change in beliefs, rather than a higher degree of uncertainty aversion.…”
Section: Application 3: Situational Factorsmentioning
confidence: 99%
“…While less is known about changes in financial risk taking and mood, we know that positive mood states have been associated with more conservative behavior in risky tasks involving financial rewards [21][22][23]. There is market evidence that even professional traders change their investment strategies (increase short selling) on more cloudy days [12]. ambiguity aversion probability equivalent for an ambiguous gamble with 50% wining probability cloudiness (0 for clear sky to 9 maximum coverage) precipitation, sunshine and temperature 0.12 increase no effect…”
Section: Risk Attitudementioning
confidence: 99%
“…At an economic level, there is also now some direct evidence that light levels influence human choice. A growing body of literature has shown, for example, that weather and seasons affect economic outcomes in financial markets [9][10][11][12][13][14]. Table 1 summarizes what we have learned so far in terms of the impact of weather on financial decision-making.…”
Section: Introductionmentioning
confidence: 99%